Hubungan Antara Stres Akademik dengan Prokrastinasi Akademik pada Mahasiswa di Masa Pandemi Covid-19 - Chornelia Silintowe Labiro; Ratriana Y.E. Kusumiati (Bulletin of Counseling and Psychotherapy, 2022)
The purpose of this study was to determine the relationship between academic stress and academic procrastination in psychology students of the 2018 SWCU class during the covid-19 pandemic. The type of research used is quantitative research with a correlational design, using the Accidental Sampling technique which is part of the non-probability sampling technique. The participants in this study were psychology students from the 2018 Satya Wacana Christian University with 86 students. The research variables were measured using two scales, namely the Adult Inventory of Procrastination scale developed by Steel, which was used to measure the academic procrastination scale and the Educational Stress Scale for Adolescent scale which was used to measure academic stress developed by Sun, Hou, and Xu. Data analysis used the Pearson product moment correlation method. The results showed a significant positive relationship between academic stress and academic procrastination with r = 0.635 and a significance of 0.000 (p <0.05). It can be interpreted that the hypothesis in this study is accepted. the higher the academic procrastination, and vice versa, the lower the academic stress, the lower the academic procrastination in psychology students from the 2018 Satya Wacana Christian University.